Fire and herbivory effects on soil organic carbon stocks and soil greenhouse gas emissions from South African grasslands and savannas: Implications for global change - Chikomba, Farai (Department of Biological Sciences, 2023)
Understanding drivers of soil organic C (SOC) stocks and soil greenhouse gas emissions in grassland and savanna ecosystems is critical for climate change mitigation considering that soils are large C reservoirs while functioning as sinks and sources of the principal soil greenhouse gases, carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O). We however, have limited understanding of how wildlife herbivory, fire and pyric-herbivory influence SOC stocks and soil greenhouse gas emissions in these ecosystems. We hypothesised that, in low nutrient soils, wild herbivores would shift vegetation towards low quality (high C:N) foliage and litter that are resistant to microbial decomposition. This may contribute to the stable SOC pool, while reducing fluxes of all soil greenhouse gases. By contrast, fire was expected to reduce soil N pools by volatilisation, but to increase the stable SOC pool by addition of mostly recalcitrant pyrogenic organic C, thereby lowering CO2 and N2O fluxes. CH4 fluxes would be increased by the fire induced death of methanotrophic bacteria. To explore this, we examined SOC stocks, soil CO2, CH4 and N2O fluxes including other soil and environmental variables from Long-Term Ecological Research sites within a South African grassland and savanna. Four fire treatments distinguished by fire frequency were used (annual, biennial, triennial and no fire) while the presence or absence of wild herbivores represented the two herbivory treatments. We found that grassland SOC stocks were highest with biennial fires (20.47 ± 2.04 g C m-2, p < 0.001) compared to other treatments. In the same site, soil CO2 fluxes were highest with herbivory plus annual fires (2.28 ± 0.72 µmol m-2 s-1, p < 0.001). In the savanna, neither SOC stocks nor soil CO2 fluxes were affected by treatments. Generally, lower frequency fires (biennial or triennial) increased soil CH4 uptake while annual fires reduced soil CH4 uptake. From this, we estimated that South African grassland and savanna soils could consume about 0.47% per m2 of the CH4 released by global wetlands. These native grassy sites with wildlife exhibited very low fluxes of N2O whereas tropical grasslands and savannas that include livestock populated rangelands are thought to contribute about 16% to the global terrestrial N2O emissions. Linear mixed-effects models for SOC stocks showed total soil N was the strongest predictor rather than plant detritus inputs. Thus, we conclude that fire and herbivory drove SOC stocks via effects on soil N. After pooling the data for the grassland and savanna to compare with local and global figures, we conclude that South African grasslands and savannas have a small but significant potential for SOC sequestration and reduction of soil greenhouse emissions given that they constitute ca. 57% of the country's terrestrial ecosystems.